2017
DOI: 10.1097/ccm.0000000000002067
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effect of Different Doses of Fluids for a Fluid Challenge: A Quasi-Randomized Controlled Study

Abstract: Objective: The objectives of this study are to determine what is the minimal volume required to perform an effective fluid challenge (FC) and to investigate how different doses of intravenous fluids in a FC affect the changes in cardiac output and the proportion of responders and non-responders.Design: quasi-randomised controlled trial. Setting: Cardiothoracic intensive care unit, tertiary university hospitalPatients: 80 Post-cardiac surgery patients.Intervention: intravenous infusion of 1, 2, 3 or 4 mL/Kg (bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 23 publications
3
59
1
7
Order By: Relevance
“…the increase in mean circulating filling pressure (MSFP) must be greater than the increase in CVP [15]. In a dose titration study performed in post cardiac surgery patients, the authors demonstrated that a fluid bolus of about 300 mL is required to reliably increase MCFP [20]. In septic patients with an increased unstressed volume it is likely that a 500 mL fluid bolus would achieve the same effect.…”
Section: Potential Dangersmentioning
confidence: 99%
“…the increase in mean circulating filling pressure (MSFP) must be greater than the increase in CVP [15]. In a dose titration study performed in post cardiac surgery patients, the authors demonstrated that a fluid bolus of about 300 mL is required to reliably increase MCFP [20]. In septic patients with an increased unstressed volume it is likely that a 500 mL fluid bolus would achieve the same effect.…”
Section: Potential Dangersmentioning
confidence: 99%
“…The higher heart rate and the numerically increased MAP in patients demonstrating a decrease in P arm compared to patients in whom P arm increased is consistent with increased baseline sympathetic activity that could have been attenuated by the fluid bolus. The variable response of P arm to fluid loading has been reported in post‐cardiac surgery patients, although fluid volumes similar to the 500 mL of this study generally increased P arm . The dynamic responses in vascular compliance illustrate the complexity of predicting volume responsiveness in patients and highlights the importance of P arm and its interpretation to evaluate and quantify the intravascular volume state.…”
Section: Discussionmentioning
confidence: 59%
“…Although the operational conditions of laparoscopic cholecystectomy includes pneumoperitoneum and the reverse Trendelenburg position and both can cause an excessive preload-dependent state, considering laparoscopic cholecystectomy is a less-invasive surgery with minimal bleeding risks, the volume for conventional fluid responsiveness test can be relatively large and may cause a volume overload postoperatively. Although the mini-volume test uses relatively small volumes, it has been used in many previous studies and showed good results [17][18][19].…”
Section: Discussionmentioning
confidence: 99%